PENGARUH BRAND EQUITY DAN KUALITAS LAYANAN INTERNET BANKING TERHADAP LOYALITAS NASABAH PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK CABANG JENEPONTO - Andi Widiawati (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The purpose of this study was to determine the effect of brand equity and service quality on customer loyalty. The data used in this study was obtained from questionnaires and some direct observation and interviews with relevant parties. From this study it can be concluded based on statistical test that variable brand equity and quality of service together (simultaneous-test F) have a positive influence on customer loyalty variable. Based on T test, variable brand equity (X1) and quality of service (X2) has a positive effect with a significant level of each variable customer loyalty (Y).